Evaluation of pomegranate varieties under semi-arid environment of central Gujarat (Indian Journal of Arid Horticulture, 2021)
Pomegranate (Punica granatum L.) belongs to the family Punicaceae, widely grown in the moderate climate of the Mediterranean region and it is well adapted to arid and semi-arid soils, and their trees grow successfully under unfavorable climatic and soil conditions and considered as salinity resistant plant (Ibrahim, 2016). Owing to its high nutritive value, wider adaptability to diverse agro-climatic conditions, early and prolific bearing with a high monetary return, pomegranate is becoming popular as a commercial crop in western part of India. In Gujarat, it occupies an area of 30.51 thousand ha with an annual production of 0.46 MT and it is mainly grown in Kachchh, Banaskantha and Mehsana districts; the average productivity is 15.13t/ha (Anonymous, 2018). Pomegranate is grown in many states of India like Maharashtra, Gujarat, Rajasthan, Uttar Pradesh, Haryana, Andhra Pradesh, Karnataka and Tamil Nadu and to a limited extent in Jammu and Kashmir, Himachal and Uttarakhand. Pomegranate possesses drought hardiness, offers immense potential to grow under marginal lands. As a result it is gaining popularity among farmers all over the country particularly in rain-fed areas (Verma et al., 2013). Several old varieties are under cultivation in this region but evaluation and recommendation regarding their suitability for this region has not been done. In this regard present work was carried out to know the plant growth and physico-chemical properties of different important varieties in this region.
Keywords: Pomegranate; Jammu and Kashmir; farmers